Sensitivity of a leaf gas-exchange model for estimating paleoatmospheric CO2 concentration - D. L. Royer; K. M. Moynihan; M. L. McKee; L. Londoño; P. J. Franks (Climate of the Past, 2019)
Leaf gas-exchange models show considerable promise as paleo-CO2 proxies. They are largely mechanistic in nature, provide well-constrained estimates even when CO2 is high, and can be applied to most subaerial, stomata-bearing fossil leaves from C3 taxa, regardless of age or taxonomy. Here we place additional observational and theoretical constraints on one of these models, the “Franks” model. In order to gauge the model's general accuracy in a way that is appropriate for fossil studies, we estimated CO2 from 40 species of extant angiosperms, conifers, and ferns based only on measurements that can be made directly from fossils (leaf δ13C and stomatal density and size) and on a limited sample size (one to three leaves per species). The mean error rate is 28 %, which is similar to or better than the accuracy of other leading paleo-CO2 proxies. We find that leaf temperature and photorespiration do not strongly affect estimated CO2, although more work is warranted on the possible influence of O2 concentration on photorespiration. Leaves from the lowermost 1–2 m of closed-canopy forests should not be used because the local air δ13C value is lower than the global well-mixed value. Such leaves are not common in the fossil record but can be identified by morphological and isotopic means.